Abject joy: Paul, prison, and the art of making do - Schellenberg, Ryan S. (Oxford University Press USA - OSO, 2021)
Abject Joy is a social history of prison in the Greek and Roman world that takes Paul's letter to the Philippians as its focal instance--or, to put it the other way around, a study of Paul's letter to the Philippians that takes the reality of prison as its starting point. Examining ancient perceptions of confinement, and placing this ancient evidence in dialogue with modern prison writing and ethnography, it describes Paul's urgent and unexpectedly joyful letter as a witness to the perplexing art of survival under constraint.